An Open-Frame Loading Stage for High-Resolution X-Ray CT - David Plappert; Michael Schütz; Georg C. Ganzenmüller; Frank Fischer; Mario Campos; Simon Procz; Michael Fiederle; Stefan Hiermaier (Instruments)
The utilisation of high-resolution in situ computed tomography (CT) in the (sub-)μm range is typically only viable in synchrotron facilities, as the deployment of a conventional loading stage in laboratory CTs with a cone beam source does not facilitate a corresponding geometric magnification. This publication presents a CT system with a novel in situ concept that allows spatial resolutions down to 0.5 μm, enabling the analysis of weakly absorbing materials capable of applying loads of up to 5 kN in both the compression and tension directions to the sample during the measurement. The necessity for a highly precise mechanical design to ensure successful measurements at magnifications approaching the theoretical limit makes the system’s development particularly demanding. The components employed are presented, along with the requisite considerations and methodologies. It can be demonstrated that the intended specifications with regard to precision and quality are met. The experimental results of a fibre-reinforced polymer demonstrate the system’s ability to detect matrix damage features below a single fibre diameter, thereby highlighting its potential for applications in materials science where traditional laboratory CTs are insufficient and synchrotron access is limited.